THE RELATIONSHIP OF NATURE AND CULTURE: NATURE AS A CULTURAL VALUE - Lobar Mukhtarova (Journals Park Publishing, 2025)
The article discusses the basic concepts of environmental education, the importance of environmental protection, reveals modern methods of developing environmental consciousness, including environmental education, education, culture and also educational activities.
Keywords: Environmental education and upbringing, culture, the world around us, natural sciences, natural literacy.